OPERASI TERBUKA PARA INFLUENCER DI TENGAH RENDAHNYA LITERASI KHALAYAK - Ghassani, Rizki (KOMUNIKA BANGSA, 2025)
A convincing style of speech combined with supportive gestures creates its own appeal. In a scene on a social media screen, photos and videos highlight objects in close-up with an appetizing effect. Someone appears, acting like an expert who then reviews the product he endorses. Instantly the audience is captivated. However, they do not realize that they are trapped in a persuasion trap spread by the influencers. Whatever is conveyed is able to hypnotize even though if digested more deeply there is an essential error in the meaning of the product. However, because they have been persuaded by the invitation, they secretly note down the address of the culinary product. This is the marketing communication model in the digital era. To further examine the activities of influencers, this study aims to analyze the conditions of the audience who are directly influenced by the invitation of influencers. The approach used in this study is a qualitative method with a narrative analysis type. The results of the study show that the level of audience literacy is still relatively low, resulting in a persuasive effect that moves the audience to make decisions, while in a society with a high level of literacy, it will not be easily influenced by the persuasion conveyed by influencers.